Effects of age on the physiological and mechanical characteristics of human femoropopliteal arteries. (1st January 2015) - Kamenskiy, Alexey V.; Pipinos, Iraklis I.; Dzenis, Yuris A.; Phillips, Nicholas Y.; Desyatova, Anastasia S.; Kitson, Justin; Bowen, Robert; MacTaggart, Jason N.
Graphical abstract: Abstract: Surgical and interventional therapies for peripheral artery disease (PAD) are notorious for high rates of failure. Interactions between the artery and repair materials play an important role, but comprehensive data describing the physiological and mechanical characteristics of human femoropopliteal arteries are not available. Fresh femoropopliteal arteries were obtained from 70 human subjects (13–79 years old), and in situ vs. excised arterial lengths were measured. Circumferential and longitudinal opening angles were determined for proximal superficial femoral, proximal popliteal and distal popliteal arteries. Mechanical properties were assessed by multi-ratio planar biaxial extension, and experimental data were used to calculate physiological stresses and stretches, in situ axial force and anisotropy. Verhoeff–Van Gieson-stained axial and transverse arterial sections were used for histological analysis. Most specimens demonstrated nonlinear deformations and were more compliant longitudinally than circumferentially. In situ axial pre-stretch decreased 0.088 per decade of life. In situ axial force and axial stress also decreased with age, but circumferential physiological stress remained constant. Physiological circumferential stretch decreased 55–75% after 45 years of age. Histology demonstrated a thickened external elastic lamina with longitudinally oriented elastin that was denser in smaller, younger arteries. Axial elastin likely regulates axial pre-stretch to help accommodate the complex deformations required of the artery wall during locomotion. Degradation and fragmentation of elastin as a consequence of age, cyclic mechanical stress and atherosclerotic arterial disease may contribute to decreased in situ axial pre-stretch, predisposing to more severe kinking of the artery during limb flexion and loss of energy-efficient arterial function.